The point of it all : essays on Jesus Christ - O'Neill, J. C. (Theological Seminar Series, 2000)
The atheism of modern thought is based on irrational assumptions...First-century Jews expected a suffering Messiah...Jesus knew it was he...Jesus' birth and resurrection in history . The point of the parables...The point of Christology...The historical grounds for scepticism about Christian claims concerning Jesus Christ rely on misreadings of the Bible. In a series of original essays, the author issues a formidable challenge to many of the presuppositions of modern theology.